IMPROVING STUDENTS SPEAKING LEARNING PROCESS THROUGH ROUND ROBIN TECHNIQUE - Firmansyah, Arifa'i Hadi (JOEEL (Journal of English Education and Literature), 2021)
This research is a classroom action research. It is aimed to find out how well Round Robin Technique in improving students speaking learning process method to solve the problems faced by the students. This research conducted at the Tenth Grade Students of SMAIT Al Fityan. Through observation checklist and field note, the students action was observed and reflected in each cycle. From the process of this study, the finding shows that there were good impacts toward students speaking. Most of students were interested and enthusiastic in the teaching and learning process. Based on the observation in the implementation of Round Robin technique, it showed that encouraging students to be active in sharing their ideas through Round Robin technique was able to improve students ability in speaking. In addition, this technique also helped the students to enlarge their vocabulary by opening dictionary, discussing together with group or asking to the teacher. The result of this research showed that the students activeness in participation of each cycle has improved during their discussion and performance of speaking learning process. Therefore, Round Robin Technique could help the teacher in teaching and learning process because this method encouraged students to learn actively.